Efficient Vocabulary Testing Techniques - Mykhailiuk, L. (Journal of Vasyl Stefanyk Precarpathian National University, 2016)
The article deals with the problem of teaching vocabulary. Different aspects of vocabulary (pronunciation, spelling, grammar, collocation, meaning, word formation) are considered alongside with efficient vocabulary testing techniques